2017
DOI: 10.3390/molecules22111915
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic Acid and Its Derivatives: Biological Activities and Therapeutic Potential in Chronic Diseases

Abstract: The increasing demand for natural products as an alternative therapy for chronic diseases has encouraged research into the pharmacological importance of bioactive compounds from plants. Recently, there has been a surge of interest in the therapeutic potential of oleanolic acid (OA) in the prevention and management of chronic diseases. Oleanolic acid is a pentacyclic triterpenoid widely found in plants, including fruits and vegetables with different techniques and chromatography platforms being employed in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
196
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(204 citation statements)
references
References 98 publications
2
196
0
6
Order By: Relevance
“…Recommendations regarding overall diet composition, increased physical activity, weight loss, moderate consumption of alcohol and avoiding tobacco were given identically to both groups. This strong protective action against diabetes in humans is consistent with experimental evidence in animals showing improvements in glucose homeostasis, lipid metabolism and insulin signalling, as well as the reinforcement of the adaptive cell response to oxidative stress and inflammation, all recognized as pharmacological mechanisms of OA …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Recommendations regarding overall diet composition, increased physical activity, weight loss, moderate consumption of alcohol and avoiding tobacco were given identically to both groups. This strong protective action against diabetes in humans is consistent with experimental evidence in animals showing improvements in glucose homeostasis, lipid metabolism and insulin signalling, as well as the reinforcement of the adaptive cell response to oxidative stress and inflammation, all recognized as pharmacological mechanisms of OA …”
Section: Discussionsupporting
confidence: 81%
“…The pharmacological potential of OA has been shown in experimental models, but studies in humans are very scarce . A probable reason for this could be belief in its poor bioavailability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Oleanane triterpenoids are actively being developed for pharmaceutical purposes: [2] oleanolic acid is used in China to treat liver disorders [3] and synthetic oleananes have advanced to clinical trials for chronic kidney disease. [2b] Decades of research have established that the biosyntheses of these pentacyclic triterpenoids occur via polyolefin cyclization of 2,3-oxidosqualene and subsequent cationic rearrangements of the D and E rings. [46] In contrast, the pathways that reorganize the A and B rings of pentacyclic triterpenoids, as represented by the justicanes (Figure 1), [7] are not clearly understood.…”
mentioning
confidence: 99%
“…Recent research has demonstrated that OA prevents Dex-induced hypertension in rats through its antioxidant and nitric oxide releasing action. 21,22 We speculate that the combination of icariin and OA has the function of increasing protein and mRNA expression of GR. In the present study, a combination of icariin and OA was administered to investigate its potential for sensitizing GCresistant CEM-C1 cells to Dex, and the results showed that the combination could effectively sensitize GC-resistant CEM-C1 cells to Dex-induced apoptosis by activation of GR and regulate GR isoforms.…”
Section: -5mentioning
confidence: 99%